LEARNING SUPPORT NETWORK OF PARENTS WHO HAVE CHILDREN WITH LEARNING DISABILITIES (Proceedings of International Conference on Special Education, 2015)
There is a need to develop learning support networks for special educators. A case study design was chosen in order to explore answers to the question of, what factors prevent parents from giving learning support networks for their children in the special education class? The purpose of using a case study was to gain an understanding of the research question from the participants’ perspective. The case study was made up of sub-cases that were parents of children who all went to a particular school at the time of their referral for assessment of learning disabilities. The data collected through unstructured interviews were analysed using the constant comparative method. The finding that emerged as a major factor that prevented parents from seeking learning networks support when children started failing in the foundation phase was ignorance of the phenomenon of learning disabilities. The other factors that were identified related to parents’ understanding of their children’s learning disabilities; their being illiterate; and the belief in cultural issues. Recommendations were suggested for both the special educators and educational psychologist relating to the need for parent education on the learning and development of their children with specific emphasis on learning disabilities. The role parents can play to develop in learning support networks with educators was also highlighted